Evidence Obtained Through Unlawful Means During Police Custody - Mohamad Ismail Bin Mohamad Yunus (Ius Poenale)
In contemporary discussions, there is growing debate over the procedural methods employed by police in obtaining evidence from suspects while in custody. A key point of contention is whether evidence acquired through illegal means should be admitted in court, with some arguing that its admission violates the suspect's right to a fair trial, while others contend that such evidence is crucial for proving the case. The law is currently ambiguous on this issue. According to the Oxford Legal Dictionary, illegally obtained evidence is defined as evidence acquired through methods that contravene legal procedures. Importantly, the distinction between evidence obtained illegally and confessions made while in police custody is critical, as Section 26(1) of the Evidence Act 1950 explicitly prohibits the admission of confessions made under such circumstances. This article aims to explore the status of illegally obtained evidence and assess whether it should be admitted or excluded by the courts when the evidence is obtained from a suspect in police custody.